PENGEMBANGAN MEDIA DIGITAL WORDWALL ‘RAKATA’ PADA KETERAMPILAN MEMBACA SISWA KELAS II SDN 55 PALEMBANG - Pallaya, Dini; Murniviyanti, Liza; Anisah Utami, Sonia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low reading skills of second-grade students at SDN 55 Palembang, where it was found that students were still unable to read properly, thereby hindering the learning process. This study is based on the theory of Indonesian language learning in elementary schools and the use of interactive digital media, specifically WordWall, as a tool to improve reading skills. This study employed the research and development (R&D) method using the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, documentation, and questionnaires. The developed product is a digital WordWall called ‘Rakata,’ which features activities where students arrange letters into wordsbased on images. The research results indicate that the developed media exhibits a very high level of validity, with an average percentage exceeding 94% from experts in media, content, and language. Practicality testing showed very practical results with a percentage of 92.4% in one-on-one testing and 86.85% in small group testing, as well as a 77% teacher response rate. Thus, the ‘Rakata’ Wordwall media is deemed valid and practical for use in improving the reading skills of second-grade students.